Integrated Production of Biodiesel and Concentration of Polyunsaturated Fatty Acid in Glycerides Through Effective Enzymatic Catalysis - Ma, Gaojian; Dai, Lingmei; Liu, Dehua; Du, Wei (Frontiers in Bioengineering and Biotechnology, 2019)
Abstract: DHA (docosahexaenoic acid) and EPA (eicosapentaenoic acid), contained in glycerides has been reported to be more advantageous for their intake than its counterpart in the form of free fatty acid or fatty acid esters. This work attempt to achieve the flexible concentration of DHA and EPA in glycerides as well as biodiesel production via a two-step process catalyzed by lipases. In the first step, several commercial lipases were investigated and Novozym ET2.0 demonstrated the highest potential in selective concentration of DHA and EPA. Over 85% of EPA and other fatty acids were converted to its corresponding FAEEs (fatty acid ethyl esters), while over 80% of DHA remained in glycerides under the optimized conditions. After the first step ethanolysis, the oil phase was subject to molecular distillation and a 97.5% biodiesel (FAEE) content could be obtained. Further flexible enrichment of DHA and EPA in glycerides was realized by immobilized lipase Novozym 435-mediated transesterification of glycerides (remaining in the heavy phase after molecular distillation) with DHA or EPA-rich EE, and glycerides with 67.1% DHA and 13.1% EPA, or glycerides with 41.1% EPA and 38.0% DHA could be obtained flexibly. This work demonstrated a novel process for the thorough utilization of fish oil, with which the combined production of biodiesel as well as the flexible enrichment of DHA and EPA in glycerides could be achieved effectively.